Corporate governance development in privately held family businesses: a multiple case analysis - Hannemann, Philipp (2014)
The objective of this study is to better understand and illustrate the process and the motivations for corporate governance implementation in Brazilian privately held family businesses. Three case companies were analyzed through an adapted developmental framework to illustrate the progression in corporate governance in response to changes in the ownership, investment and management dimensions over time. In this development, causal relationships between corporate governance and the three other framework dimensions were identified. It was found that the analyzed companies´ corporate governance implementation was motivated by the need to curb agency costs, whereas a cornerstone in this development was the first generational change. Only after the family businesses have reached the necessary maturity on all three dimensions, corporate governance practices were implemented. Put simply, the analyzed case companies developed formal systems as they grew more complex. This study complements the academic discussions on corporate governance in family businesses by offering Brazilian evidence on its underlying motivations and sequential implementation over time.